Exploring the Factors Influencing Shrimp Farmers’ Adoption Intentions toward Improved Disease-Prevention Technologies - Azali Sazali, Amira Hanani; Kamarulzaman, Nitty Hirawaty; Man, Norsida (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
Shrimp production is adversely affected by diseases, particularly in giant tiger prawn and whiteleg shrimp. The predominant use of inexpensive antibiotics by shrimp farmers has resulted in antibiotic overuse and antimicrobial resistance (AMR) at the farm level. However, the adoption of new antibiotic-related technologies remains low due to their high cost and farmers’ reluctance. This study explored key factors influencing shrimp farmers’ intentions to adopt improved disease-prevention technologies. Stratified random sampling selected 123 shrimp farmers from four regions in Peninsular Malaysia, and data were collected through a structured questionnaire. Several statistical analyses were employed to scrutinize the collected data, encompassing descriptive analysis, Chi-square analysis, factor analysis, and logistic regression analysis. The research findings revealed a significantly high intention (74.0%, n=91) among shrimp farmers toward adopting improved disease-prevention technologies. The analysis unveiled a significant correlation between attitude (ß=2.062, p<0.000) and the intention of shrimp farmers toward adopting improved disease-prevention technologies in their shrimp farming practices. Notably, those with a positive attitude were found to be 7.9 times more interested in adapting these technologies, underlining attitude as the predominant influence in this context. These findings offer valuable insights to enhance the competitiveness of the aquaculture sector in shrimp production and animal health advancements. Promoting sustainable and responsible practices has become the key to ensuring the shrimp farming sector’s long-term success and resilience.